2021
DOI: 10.1172/jci146221
|View full text |Cite
|
Sign up to set email alerts
|

Pfs230 yields higher malaria transmission–blocking vaccine activity than Pfs25 in humans but not mice

Abstract: Background. Vaccines that block human-to-mosquito Plasmodium transmission are needed for malaria eradication and clinical trials have targeted zygote antigen Pfs25 for decades. We reported that a Pfs25 protein-protein conjugate vaccine formulated in alum adjuvant induced significant serum functional activity in both US and Malian adults. However, antibody levels declined rapidly, and transmission-reducing activity required four vaccine doses. Functional immunogenicity and durability must be improved before adv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 36 publications
2
75
1
Order By: Relevance
“…Transmission-blocking activity of antibody against Pfs230 is known to be dependent on antibody mediated complement fixation 25 , 35 . Hence Pfs230 vaccines that generate antibody subclasses that facilitate complement activation may provide higher functional activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission-blocking activity of antibody against Pfs230 is known to be dependent on antibody mediated complement fixation 25 , 35 . Hence Pfs230 vaccines that generate antibody subclasses that facilitate complement activation may provide higher functional activity.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies in mice showed induction of IgG2, that facilitate complement activation in mice, resulted in superior functional activity for Pfs230 conjugate vaccines 32 . Pfs230-EPA conjugate formulated in Alhydrogel ® generated complement fixing IgG1 in humans and Rhesus and showed transmission-blocking functional activity 35 . Therefore, we analyzed the IgG subclass distribution of Pfs230D1-EPA/ALFQ at different time points to evaluate its role in the transmission-blocking activity of this vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…Although this vaccine approach does not offer any direct clinical protection in humans, blocking malaria transmission is an essential component of effective control and elimination strategies. There has been limited progress for transmission-blocking vaccines, with one candidate based on the gametocyte surface antigen, Pfs230 (Pfs230D1M), showing promise in early clinical trials and a phase 2 clinical trial is ongoing in Mali (NCT03917654) 13 .…”
Section: Developing Vaccines That Block Malaria Transmissionmentioning
confidence: 99%
“…In USA adults, two vaccine doses induced functional activity in Pfs230D1M-EPA/Alum volunteers, but no significant activity in Pfs25-EPA vaccine recipients, and combination with Pfs25-EPA did not increase functional activity over Pfs230D1M-EPA alone. The research group concluded that the functional activity of Pfs230D1M-EPA is significantly superior to that of Pfs25-EPA ( Healy et al, 2021 ). For more information about the clinical development of these falciparum TBVs, please refer to two recent review articles ( Miura et al, 2019 ; Duffy, 2021 ).…”
Section: Tbv Development Efforts To Datementioning
confidence: 99%